2016
DOI: 10.1080/10669817.2016.1230352
|View full text |Cite
|
Sign up to set email alerts
|

Spinal manipulation does not affect pressure pain thresholds in the absence of neuromodulators: a randomized controlled trial

Abstract: This study suggests that in young adults who do not have current or recent symptoms of spinal pain, multiple within-session treatments of cervical and lumbar spinal manipulation fail to influence PPTs. Changes in PPT that are observed in symptomatic individuals are likely to be primarily influenced by pain-related neuromodulators rather than by an isolated, mechanical effect of spinal manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…However, PPTs were significantly increased immediately after SM at the most sensitive segment (Nim et al., 2020). This supports the segmental effects of SM on pain‐related processes, which may rely on the modulation of central sensitization (Jordon et al., 2017), as discussed below.…”
Section: Mechanisms Of Pain Relief By Smsupporting
confidence: 79%
“…However, PPTs were significantly increased immediately after SM at the most sensitive segment (Nim et al., 2020). This supports the segmental effects of SM on pain‐related processes, which may rely on the modulation of central sensitization (Jordon et al., 2017), as discussed below.…”
Section: Mechanisms Of Pain Relief By Smsupporting
confidence: 79%
“…Previous studies have shown that individuals with cLBP often respond differently than asymptomatic individuals to symptom-modulating interventions. For example, while spinal manipulation seems to have minimal effect on pressure-pain thresholds (PPTs) in asymptomatic individuals, 32 , 33 it routinely increases PPT in individuals with chronic pain. 34 , 35 , 36 However, the response to manual therapy on dynamic measures of pain regulation seem to be more consistent.…”
Section: Discussionmentioning
confidence: 99%